Partial monosomy of 7q32 in a case of de novo rcp(7;15)(q32;q15). Issue 5 (May 1994) - D'Alessandro, E; Ligas, C; Lo Re, M L; Marcanio, M P; Gentile, T; Del Porto, G
Abstract : A de novo apparently balanced translocation between chromosomes 7 and 15 with breakpoints in q32 and q15 respectively is reported in a female child. Clinical features included general growth and psychomotor retardation, feeding problems, microcephaly, low set ears, a short neck, and brachydactyly. These findings suggested possible physical or functional partial monosomy of the 7q32 or 15q15 segments. The phenotype of this case is similar to other cases of 7q deletion.